Efeitos da tração no funículo espermático sobre o testículo, epidídimo e ducto deferente de ratos - Salomão Brêtas (2015)
The surgical treatment of indirect inguinal hernias and cryptorchidism involve intraoperative traction on the spermatic cord. The aim of the present experiment was to investigate the lesions that may occur in the testis, epididymis and vas deferens as a result of traction applied to the spermatic cord of rats. Forty adult male Wistar rats were randomly allocated into four groups of 10 animals. A traction force of 1.6 N and 1 N was applied to the right spermatic cord of the animals in group I and II, respectively. Group III was the sham, and group IV served as the control. Testicular volume was measured before and after the application of traction using ultrasonographic and caliper measurements. Comparisons of variables and between groups were done using the F (ANOVA) and Kruskal-Wallis tests with the level of significance set at 5%. The evaluation of right testes according to Kolbes histological grading showed higher histological grades for group I compared to the other groups, with group IV exhibiting lower histological grades than groups II and III. For the left-side testes, both groups III and IV showed lower histological grade lesions than groups I and II. Final right testicular volume in group IV as measured by the calipers was greater than in groups I, II, and III. On the left side, testicular volume was smaller in group I than in groups III and IV. Ultrasonography revealed that final testicular volume on the right side was greater in group IV than in groups I and III. There was moderate agreement and a positive correlation, which were both significant regarding the percent reduction in right testicular volume on ultrasound and by caliper measurements in the rats of groups I, II, and III. Right-side testicular necrosis was identified in 50% of the rats in group I and 40% of those in group III. Final right testicular weight was greater in the group IV rats than that for the other groups. In the right epididymis, 71.8% of the rats showed reduced intraluminal sperm, which was absent in 5% of the animals. In the left epididymis, 37.5% of the rats showed a reduction in intraluminal sperm. Fewer Sertoli cells, necrosis, and decreased germ cells in the seminiferous tubules were found in the testes. Final testicular volume was reduced. Final weight of the right testis was decreased. Epididymal sperm count was reduced. No muscle layer thickness reduction, inflammation, rupture, or mucosal injury were found in the vas deferens. Traction to the spermatic cord compromised the structure and function of the testicle and epididymis of rats. Intraoperatively, gentle handling of the spermatic cord, testicle, and epididymis is critical to prevent injury to those structures.